1. Investigation of “Kien ty chi thong - HV” granules for acute and subchronic oral toxicity in experimental animals - Quan, Hoang Trong; Phuong, Pham Thuy; Binh, Pham Quoc; Anh, Pham Thi Van; Hang, Dinh Thi Thu (Tạp chí Nghiên cứu Y học, 2023)
This research is to evaluate the acute and subchronic toxicities of “Kien ty chi thong - HV” granules through oral administration in experimental animals. The acute toxicity was determined by Litchfield Wilcoxon method in Swiss mice. The subchronic toxicity was evaluated by WHO and OECD’s recommendation in Wistar rats with oral doses of 1.8 g/kg/day (equal to recommended human dose) and 5.4 g/kg/day (3 times as high as recommended human dose) in 4 consecutive weeks. As a result, “Kien ty chi thong - HV” granules at the highest dose used in mice (56.25 g/kg) did not express acute toxicity in mice. In terms of the subchronic toxicity test, after oral administration of “Kien ty chi thong - HV” granules, hematological parameters, hepato-renal functions, and microscopic images of liver and kidney were unchanged as compared with the control group. In conclusion, “Kien ty chi thong - HV” granules did not produce acute and subchronic toxicities in Swiss mice and Wistar rats.